2017
DOI: 10.1007/s11914-017-0374-z
|View full text |Cite
|
Sign up to set email alerts
|

Connexins and Pannexins in Bone and Skeletal Muscle

Abstract: Purpose of review To discuss the current knowledge on the role of connexins and pannexins in the musculoskeletal system. Recent findings Connexins and pannexins are crucial for the development and maintenance of both bone and skeletal muscle. In bone, the existence of connexin and more recently pannexin channels in osteoblasts, osteoclasts, and osteocytes has been described, and shown to be essential for normal skeletal development and bone adaptation. In skeletal muscles, connexins and pannexins play import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 104 publications
0
30
0
Order By: Relevance
“…Connexins and pannexins are other adhesion mediators that form gap junctions and are involved in mechanotransduction and consecutive ATP secretion in both bone and muscle, especially as an important system in osteocytes. Connexin 43 has functions beyond the physical mechanotransduction between cells, since its knockout in early osteoblasts causes impaired muscle formation in mice [28,29].…”
Section: Mechanosensing and Mechanotransductionmentioning
confidence: 99%
“…Connexins and pannexins are other adhesion mediators that form gap junctions and are involved in mechanotransduction and consecutive ATP secretion in both bone and muscle, especially as an important system in osteocytes. Connexin 43 has functions beyond the physical mechanotransduction between cells, since its knockout in early osteoblasts causes impaired muscle formation in mice [28,29].…”
Section: Mechanosensing and Mechanotransductionmentioning
confidence: 99%
“…ATP release and P2 receptor signaling are key modulators of skeletal development and homeostasis. Pannexin and connexin channels, P2X and P2Y receptors were detected in osteoblasts, osteoclasts, and osteocytes (Orriss et al, 2006;Plotkin et al, 2017). In osteoblasts mRNA for P2Y and P2X receptors were detected and it has been shown that their expression, as well as the amount of ATP released, depends on cellular differentiation status since osteoblasts' responsiveness to nucleotides increase in parallel with the cell differentiation and an increase of P2Y2 and P2X4 receptors was detected in mature osteoblasts compared to immature cells (Bowler et al, 1995;Maier et al, 1997;Hoebertz et al, 2000;Ihara et al, 2005;Orriss et al, 2006;Orriss et al, 2009;Orriss et al, 2012;Syberg et al, 2012).…”
Section: P2 Receptorsmentioning
confidence: 99%
“…Prostaglandin E2 (PGE2), a potent inflammatory cytokine produced by multiple cell types and released to the stem cell niche after muscle injury, has recently emerged as key regulator which promotes myogenic stem cell expansion and muscle regeneration, showing great potential as therapeutic target in repairing large skeletal muscle defect [47]. Among those efforts that have been made toward the elevation of PGE2, SW033291 stands out as a promising candidate.…”
Section: Discussionmentioning
confidence: 99%